A rapid deployment valve option for failing Medtronic Freestyle full root: a single centre experience - Solveig Moss Kolseth; Sahrai Saeed; Pirjo-Riitta Salminen; Vegard Skalstad Ellensen; Venny Lise Kvalheim; Abukar Mohamed Ali; Rune Haaverstad (Journal of Cardiothoracic Surgery)
Abstract Background There are several high-risk treatment options for valve failure of a biological full root replacement. When tailoring the best treatment option for the patient, implantation of a rapid deployment valve (RDV) should be considered. Case presentation Six patients presented with aortic regurgitation in a full root Freestyle bioprosthesis. Three had a history of valve endocarditis, while the remaining had non-infectious structural valve deterioration with leaflet and commissural tears. All patients were treated with a rapid deployment EDWARDS INTUITY Elite valve. Follow-up was complete for all patients. Postoperative echocardiography showed well-functioning valve prostheses with no paravalvular leaks and acceptable pressure gradients. Echocardiographic follow-up demonstrated excellent pressure gradients and a considerable decrease in the left ventricular mass index and left ventricular end-diastolic dimensions. Follow-up cardiac CT showed no signs of coronary obstruction or other pathology. During a median follow-up of 30 months neither biological valve failure, nor any events within the composite endpoint of major adverse cardiac and cerebrovascular events occurred. Conclusions This case series presents the EDWARDS INTUITY valve as a good treatment option in patients with failing Freestyle roots.